Rosemary: A Natural Way to Improve Brain Health and Cognitive Function - Mohd.Wasiullah; Piyush Yadav; Pratibha Devi Maurya; Ruby Yadav (International Journal of Brain Sciences, 2025)
Cognitive decline is a common consequence of aging, often leading to diminished quality of life. Although conventional drug treatments, such as anticholinesterase inhibitors, are available for managing cognitive decline, they are not always effective in older adults and may even induce adverse effects. As a result, there has been growing interest in natural alternatives, particularly traditional herbal medicines, for their potential cognitive-enhancing properties. Among these, Rosmarinus officinalis (Rosemary) has gained attention due to its rich phytochemical profile, which includes phenolic compounds, terpenoids, and flavonoids with notable antioxidant, anti-inflammatory, and neuroprotective properties. This review explores the mechanisms through which Rosemary supports brain health, such as by protecting neurons from oxidative stress, reducing brain inflammation, and enhancing circulation. The cognitive benefits of Rosemary, including memory improvement, increased concentration, and reduced stress, are highlighted through both scientific studies and traditional uses. The review also discusses the potential therapeutic applications of Rosemary in managing cognitive disorders and mental health. As interest in natural cognitive enhancers grows, Rosemary presents a promising candidate for future research and application in brain health.
Keywords: Cognitive health; Rosemary; Rosmarinus officinalis; herbal medicine; memory enhancement; natural remedies